2021
DOI: 10.3389/fmicb.2021.674556
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Bacterial Networks, but Not Diversity, Are Impacted by Pea-Wheat Intercropping

Abstract: Plant-plant associations, notably cereal-legume intercropping, have been proposed in agroecology to better value resources and thus reduce the use of chemical inputs in agriculture. Wheat-pea intercropping allows to decreasing the use of nitrogen fertilization through ecological processes such as niche complementarity and facilitation. Rhizosphere microbial communities may account for these processes, since they play a major role in biogeochemical cycles and impact plant nutrition. Still, knowledge on the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 102 publications
2
15
0
Order By: Relevance
“…The α-diversity of bacterial communities in the intercropping system did not differ markedly from that in the monoculture (Figure 3A), which is similar to the findings of previous studies on wheat-faba bean and wheat-pea monoculture/intercropping systems (Tang et al, 2016;Pivato et al, 2021), suggesting a conservative response of bacterial richness to planting patterns, that is, bacterial richness is independent of their neighboring plants. This is consistent with the view of Tkacz et al (2020), who found that microbial communities are more affected by roots than by soil or plant species.…”
Section: Planting Pattern and Soil Compartment Changed Microbial Co-occurrence Patternssupporting
confidence: 88%
See 2 more Smart Citations
“…The α-diversity of bacterial communities in the intercropping system did not differ markedly from that in the monoculture (Figure 3A), which is similar to the findings of previous studies on wheat-faba bean and wheat-pea monoculture/intercropping systems (Tang et al, 2016;Pivato et al, 2021), suggesting a conservative response of bacterial richness to planting patterns, that is, bacterial richness is independent of their neighboring plants. This is consistent with the view of Tkacz et al (2020), who found that microbial communities are more affected by roots than by soil or plant species.…”
Section: Planting Pattern and Soil Compartment Changed Microbial Co-occurrence Patternssupporting
confidence: 88%
“…For example, members of Firmicutes are salt-tolerant and nitrogen-fixing, which can promote plant growth (Mukhtar et al, 2017(Mukhtar et al, , 2021Solanki et al, 2020). In the rhizosphere, there was a higher abundance of psASVs from Firmicutes in intercropping systems than monoculture, but similar results were not observed in bulk soil (Supplementary Figure 4), indicating rhizosphere microbes may account for the added value of intercropping systems by recruiting more beneficial microbial communities into the rhizosphere (Pivato et al, 2021). The association between changes in Firmicutes to the monoculture/intercropping system was found in earlier studies (Zhang M. M. et al, 2018;Gong et al, 2019;Solanki et al, 2020).…”
Section: Intercropping Systems Weaken Host Effects On Root-associated Microbial Communitiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the rhizosphere microbiota of these associated plant species differed from the rhizosphere microbiota of these same plants cultivated separately ( Sun et al, 2009 ; Zhang et al, 2012 ; Wahbi et al, 2016a ; Taschen et al, 2017 ). A more complex rhizosphere bacterial network was recently shown in pea-wheat intecropping ( Pivato et al, 2021 ). Thus, we can hypothesize that the rhizosphere microbiota accounts for the increased iron uptake by intercropped plants.…”
Section: Introductionmentioning
confidence: 89%
“…The mycorrhizosphere of associated plants, formed by AMF-colonized roots and hyphae, increases microbiota functionalities ( Wahbi et al, 2016b ). Intercropping impacts the abundance, diversity, activity and co-occurrence network of rhizosphere microbial communities ( Li et al, 2016 , 2018 ; Wahbi et al, 2016a ; Duchene et al, 2017 ; Taschen et al, 2017 ; Gao et al, 2019 ; Zaeem et al, 2019 ; Liu et al, 2021 ; Pivato et al, 2021 ). This is in agreement with the well-known positive relationship between plant and microbial diversity ( Spehn et al, 2000 ; Carney and Matson, 2005 ; Qiao et al, 2012 ; Ahmad et al, 2013 ).…”
Section: Biological Levers To Promote Plant Iron Uptake and Regulate Iron Homeostasismentioning
confidence: 99%